Mobile IP technology and applications - Raab, Stefan, 1966- (Cisco Press networking technology series., 2005)
Real-world solutions for Cisco IOS® Mobile IP configuration, troubleshooting, and management First book to address the practical application of Mobile IP in real-world environments Detailed case studies show how to apply Mobile IP in real-world networksConfiguration examples demonstrate working implementations of the Cisco Mobile IP components Includes troubleshooting methodologies for common failures and best practices The Internet and mobile communications are defining how and when people access information, with cellular phones, PDAs, and laptops driving the need for ""always-on"" I.